2011
DOI: 10.1002/hep.24614
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible MicroRNA-210 augments the metastatic potential of tumor cells by targeting vacuole membrane protein 1 in hepatocellular carcinoma

Abstract: As the ''master'' microRNA that is induced by hypoxia, miR-210 is involved in multiple processes in the hypoxia pathway. However, whether miR-210 mediates hypoxia-induced tumor cell metastasis still remains unclear. Here, we demonstrate that miR-210 is frequently up-regulated in hepatocellular carcinoma (HCC) samples and promotes the migration and invasion of HCC cells. Furthermore, miR-210 can be induced by hypoxia in HCC cells and mediates hypoxia-induced HCC cell metastasis. We identify vacuole membrane pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
120
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 29 publications
2
120
0
Order By: Relevance
“…Recently, a number of cancer genes have been reported to be associated with the tumor metastasis in HCC, including CLU, KAI1, ROCK2 and TWIST [1][2][3][4]. Furthermore, we have previously identified several microRNAs that play critical roles in HCC metastasis, such as miR-30D, miR-151 and miR-210 [5][6][7]. Additionally, many signaling pathways have also been implicated in the process of HCC metastasis, including RAF/MEK/ERK pathway, WNT/ β-catenin pathway, insulin-like growth factor pathway, hepatocyte growth factor/c-MET pathway and growth factor-regulated angiogenic signaling [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of cancer genes have been reported to be associated with the tumor metastasis in HCC, including CLU, KAI1, ROCK2 and TWIST [1][2][3][4]. Furthermore, we have previously identified several microRNAs that play critical roles in HCC metastasis, such as miR-30D, miR-151 and miR-210 [5][6][7]. Additionally, many signaling pathways have also been implicated in the process of HCC metastasis, including RAF/MEK/ERK pathway, WNT/ β-catenin pathway, insulin-like growth factor pathway, hepatocyte growth factor/c-MET pathway and growth factor-regulated angiogenic signaling [8].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study confirmed that miR-210 is induced by hypoxia in hepatocellular carcinoma cells and may promote cancer cell metastasis (19). Vacuole membrane protein 1 (VMP1) has been identified as a direct target of miR-210, and downregulation of VMP1 by hypoxia has been shown to increase cancer cell migration (19,20). A separate study suggested that miRNA-103, miRNA-107, miRNA-372 and miRNA-373 may be upregulated in hypoxic conditions, through the transcriptional regulation of hypoxia inducible factor-1α.…”
Section: Discussionmentioning
confidence: 67%
“…These miRNAs have been implicated in a broad range of biological processes including cell proliferation, apoptosis, differentiation, metabolism, migration and invasion (17,18). A previous study confirmed that miR-210 is induced by hypoxia in hepatocellular carcinoma cells and may promote cancer cell metastasis (19). Vacuole membrane protein 1 (VMP1) has been identified as a direct target of miR-210, and downregulation of VMP1 by hypoxia has been shown to increase cancer cell migration (19,20).…”
Section: Discussionmentioning
confidence: 98%
“…A number of targets of miR-210 have been reported, such as vacuole membrane protein 1 (VMP1), enzyme glycerol-3-phosphate dehydrogenase 1-like (GPD1L), iron-sulfur cluster scaffold homolog (ISCU), succinate dehydrogenase complex subunit D (SDHD) and MNT [15,19,25,42,45].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that miR-210 plays an important role in regulation of cell growth, angiogenesis, invasion and apoptosis in different human tumour models [5,11]. MiR-210 expression is frequently up-regulated in a variety of solid tumours, including breast cancer [12], non-small cell lung cancer [29], head and neck cancer [8], pancreatic cancer [4], oral tumours [31], hepatocellular cancer (HCC) [42], adrenocortical carcinoma (ACC) [23], glioblastoma [26], colon cancer [24], ovarian cancer [9], malignant melanoma [22] and renal cell cancer [27]. The expression of miR-210 is found to be down-regulated in human esophageal squamous cell carcinoma (ESCC) tissues and derived cell lines [34].…”
mentioning
confidence: 99%